ANTIDIABETIC EFFECT OF COMBINED CINNAMOMUM CASSIA EXTRACT AND METFORMIN IN RATS - Assajad, Jibril Ali Syariati; Sanif, Muhammad Edial; Primanagara, Risnandya (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Diabetes mellitus is a group of metabolic diseases characterized with hyperglycemia. This metabolic dysregulation can lead to complications in many organs and even lead to death. Diabetes mellitus can be treated by giving metformin or Cinnamomum cassia. Treatment with a combination of both is expected to better reduce blood glucose levels. This study measured the effectiveness of the combination of metformin and Cinnamomum cassia extract to blood glucose.Methods: This study used Pre-Post-Test control group design using 24 random male white rats divided into 4 groups using Simple random sampling. All groups were induced by alloxan of 150 mg/kg BW, Group 1 was given aquades, group 2 was given metformin of 45 mg/kg BW, group 3 was given Cinnamomum cassia extract 200 of mg/kg BW, and group 4 was given a combination of metformin of 45 mg/kg BW extract Cinnamomum cassia of 200 mg/kg BW. Afterwards, the collected data was analyzed using paired T test and one way ANOVA along with the corresponding post-hoc.Results: The results of this study indicate the effect of administering a combination of cinnamon extract of 200 mg/kg BW and metformin of 45 mg/kg BW to blood glucose levels (p <0.05) with a glucose decrease value of 122.80 ± 2.77 mg/dl better than a single dose of metformin with a glucose reduction value of 92.68 ± 3.10 mg/dl and Cinnamomum cassia extract with a glucose decrease value of 107.16 ± 4.80 mg/dl. This is because there is a different mechanism between cinnamon extract and metformin.Conclusion: In this study, three treatments showed a different decrease in blood sugar levels. Administration of a combination of Cinnamomum cassia extract of 200 mg/kg BW and metformin of 45 mg/kg BW caused the highest decrease. These results provide an opportunity for better treatment of diabetes.